A Farmácia e a Medicina Química na Inglaterra Quinhentista: O Caso de R. Bostocke - Reis, Ivoni de Freitas (2006)
This study aims at an understanding of the pharmacy grounded on chemical medicine introduced in England in the 16th and beginnings of the 17th centuries. Although prefigurated by many others, the main work that introduced Paracelsian ideas on English soil was The Difference the Aucient Phisicke and the Latter Physicke (1585) by R. Bostocke. Nothing is known with certainty on the author, he might have been an English Paracelsian and Parlament member and our study required to research his possible biography. On the other hand, the study of medicines and processes mentioned by Bostocke demanded an understanding of the status of chemical medicine at the time. This was performed through the analysis of related works, such as Paracelsus , Oswald Croll´s, Joseph Duchesne´s and Jean Béguin´s, and the classical medicine of Conrad Gesner. Our study aimed to show that 16th century English chemical pharmacy was much more concerned with the process, purification and dosage of medicines, than with the kind of materials employed. To demonstrate our hypothesis, some remedies mostly metallic were selected and arranged in a way that would show the path followed by iatrochemists to prepare chemical remedies, eventually, in some cases, to attain the most desired one: potable gold